Who said it? Native and non-native listeners' source memory for object-speaker associations - Beck, Sara D.; Weber, Andrea (Frontiers in Language Sciences, 2024)
In two experiments, source memory for object-speaker associations was tested for listeners varying in language proficiency. Native and non-native participants of English first heard speakers name objects with prototypical color (e.g., broccoli) before they had to indicate who had previously named each object. Speakers either consistently named objects of one color, or they randomly named objects of different colors. While both listener groups associated objects with speakers successfully, in Experiment 1, with black and white images, native listeners showed an advantage in source memory in the color consistent condition over the random condition, while non-native listeners had no such advantage. The finding for non-native listeners was replicated in Experiment 2 with color images. The results confirm the role of source memory representations in communication, but also suggest that encoding object-speaker association in L2 may be less sensitive to consistent patterns in the input.